Chemistry in Traditional Cirebon Cuisine: Reconstruction of Local Knowledge into Chemical Concepts as Contextual Learning - Fatimah Khoirunisa; Woro Sumarni; Triastuti Sulistyaningsih (Universitas Negeri Semarang, 2026)
This study aims to explore and reconstruct ethnochemistry in traditional Cirebon cuisine as a source of contextual chemistry learning. The culinary items examined include nasi jamblang, empal gentong, tahu gejrot, and tape ketan. The research employs a qualitative descriptive approach with an ethnographic design through observation, interviews, documentation, and literature study. The collected data are analyzed and reconstructed into scientific chemistry concepts. The results show that the processing of traditional Cirebon cuisine contains various chemical concepts, such as starch gelatinization, protein denaturation, colloidal systems, oxidation-reduction reactions, fermentation, reaction rates, thermochemistry, protein coagulation, and Maillard reactions. Integrating these concepts into chemistry learning can enhance students’ understanding because it is contextual and closely related to everyday life. This study provides an alternative learning resource based on local wisdom that supports the implementation of the Merdeka Curriculum.